(untitled) - Samuels, Richard J. (Ithaca, 1994)
It provides a powerful argument about Japan's techno-military policies and the linkss betweeen military and civilian inđủtial development which will catalyzzy a whole range of new debates about Japan and its future.
Keywords: Nhà nước và công nghệ,National security,Technology and state,An ninh quốc gia; Nhật Bản,Japan,Japan,Nhật Bản